2020
DOI: 10.3390/ijms21114125
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog-Gli1 Signaling and Cellular Retinoic Acid Binding Protein 1 Gene Regulation in Motor Neuron Differentiation and Diseases

Abstract: Cellular retinoic acid-binding protein 1 (CRABP1) is highly expressed in motor neurons. Degenerated motor neuron-like MN1 cells are engineered by introducing SODG93A or AR-65Q to model degenerated amyotrophic lateral sclerosis (ALS) or spinal bulbar muscular atrophy neurons. Retinoic acid (RA)/sonic hedgehog (Shh)-induced embryonic stem cells differentiation into motor neurons are employed to study up-regulation of Crabp1 by Shh. In SODG93A or AR-65Q MN1 neurons, CRABP1 level is reduced, revealing a correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The D3 dopamine receptor plays a role in clinical antipsychotic response [ 36 ]. Crabp1 encodes a protein that binds retinoic acid, which is involved in the differentiation of neurons [ 37 , 38 , 39 ]. Of the 149 genes common to two or more datasets, most were shared between AM and mPFC ( n = 72), NA and mPFC ( n = 63), and AM and NAc ( n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…The D3 dopamine receptor plays a role in clinical antipsychotic response [ 36 ]. Crabp1 encodes a protein that binds retinoic acid, which is involved in the differentiation of neurons [ 37 , 38 , 39 ]. Of the 149 genes common to two or more datasets, most were shared between AM and mPFC ( n = 72), NA and mPFC ( n = 63), and AM and NAc ( n = 12).…”
Section: Resultsmentioning
confidence: 99%
“…SHH exerts a critical function on promoting cell proliferation and differentiation, maintaining the integrity of blood–brain barrier, and protecting cells from oxidative stress ( Xia et al, 2012 ). There is evidence that SHH exerts a key function on ALS ( Lin et al, 2020 ). A study found that the decrease in the expression of cellular retinoic acid–binding protein 1 (CRABP1) is correlated with motor neuron degeneration ( Lin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that SHH exerts a key function on ALS ( Lin et al, 2020 ). A study found that the decrease in the expression of cellular retinoic acid–binding protein 1 (CRABP1) is correlated with motor neuron degeneration ( Lin et al, 2020 ). SHH may elevate CRABP1 expression through mediating GLI1, which involves specific chromatin remodeling ( Lin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that RA can also directly elicit activities to modulate cytosolic signaling [14][15][16][17][18][19][20], mediated by a speci c, cytosolic RA signaling protein called Cellular retinoic acid-binding protein I (Crabp1) [21]. Our previous studies have shown that Crabp1 levels are altered in certain pathological conditions such as under neuronal stress or neuroin ammation [16,22], and in metabolic diseases and heart failure [23], suggesting a relevance to diseases. This current study reports a new functional role of Crabp1, that it regulates intercellular communication to impact on system wide homeostasis by modulating exosome secretion.…”
Section: Introductionmentioning
confidence: 99%